PELATIHAN TENTANG PAJAK PEMERINTAH PUSAT YANG BERKAITAN DENGAN ORANG PRIBADI - Viriany; Beatrice Tannessia Tandri; Steven Imanuel (Jurnal Serina Abdimas, 2025)
Tax revenue plays a vital role in supporting Indonesia’s national development. Nearly all government expenditures both routine and non-routine are financed through taxes. Without sufficient tax income, it would be impossible to fund essential public services and infrastructure. Recognizing this, the Indonesian government has initiated various reforms to improve tax administration and optimize revenue. Key policies, such as the Job Creation Law and the Tax Harmonization Law, were introduced during the COVID-19 pandemic. In 2025, the government plans to launch the Core Tax system to replace DJP Online, highlighting its commitment to strengthening tax infrastructure. Two of the most significant contributors to tax revenue are Value-Added Tax (VAT) and Income Tax, both of which are paid to the central government. Indonesia implements a self-assessment tax system, where taxpayers are responsible for calculating, paying, and reporting their taxes particularly VAT and Income Tax. Given this responsibility, a strong understanding of tax regulations is essential. Errors in calculation, payment, or reporting can result in administrative sanctions such as fines or interest charges. To promote early awareness and understanding of taxation, the PKM Team from Universitas Tarumanagara (Untar) is organizing a tax education session for high school students in the Bandengan area. The training, scheduled for May 6, 2025, will last approximately one hour. Through this initiative, it is hoped that students will gain a foundational understanding of the importance of taxes and be better prepared to fulfill their obligations as future taxpayers, whether as employees or entrepreneurs ABSTRAK Penerimaan dari pajak sangat besar fungsinya bagi negara Indonesia. Hampir semua pembayaran pemerintahan menggunakan pemasukan dari pajak. Boleh dikatakan tanpa pajak tidak dapat membiayai pengeluaran pemerintahan baik itu untuk pengeluaran rutin maupun tidak rutin. Oleh sebab itu, negara Indonesia mulai berbenah birokrasi pajak untuk mendapatkan pemasukan yang optimal dari pajak. Pemerintah mengeluarkan cukup banyak kebijakan seperti Undang-undang Cipta Kerja dan Undang-undang Harmonisasi Perpajakan pada masa pandemi covid 19 yang lalu. Tahun 2025 ini pemerintah meluncurkan Core Tax sebagai website pengganti DJP Online. Dengan adanya core tax tersebut menunjukkan keseriusan pemerintah dalam mengoptimalkan penerimaan pajak. Salah satu pajak yang memberikan sumbangan besar bagi negara adalah pajak pertambahan nilai dan pajak penghasilan. Keduanya ini adalah pajak yang dibayarkan kepada pemerintah pusat. Pemerintah Indonesia menerapkan self-assessment system di mana wajib pajak perlu menghitung, membayar dan melaporkan sendiri pajaknya terutama untuk pajak penghasilan dan pajak pertambahan nilai. Karena itu pengetahuan yang memadai mengenai perpajakan sangatlah diperlukan bagi wajib pajak. Apabila salah menghitung, membayar dan melapor maka wajib pajak dapat dikenakan sanksi administasi berupa denda bunga. Dengan beranjak kepada pemikiran tersebut, Tim PKM Untar mengajukan diri kepada salah satu SMA di Bandengan untuk melakukan pelatihan pajak sejak dini terhadap para siswa SMA. Diharapkan dengan adanya pelatihan ini, para siswa mulai memahami mengenai tujuan perpajakan dan mempersiapkan diri untuk membayar pajak di kemudian hari nanti bila sudah mempunyai penghasilan atau melakukan usaha. Pelatihan dilakukan pada tanggal 6 Mei 2025 selama kurang lebih satu jam.